EVALUATION OF PROBLEMS ENCOUNTERED BY SCHOOL ADMINISTRATORS AND TEACHERS IN THE 4+4+4 COMPULSORY EDUCATION SYSTEM - UZUN , Ramazan; YAŞAR , Şenol; KARAMAN , Durmuş; GÜNDOĞDU , Musa; KAMALI , Mustafa; AYDOĞDU , Doğan (SSD Journal, 2024)
The purpose of this study is to evaluate the research conducted to examine the problems faced by school principals and teachers regarding the 4+4+4 education system. The research method is literature review, and the scope of the study consists of laws related to the topic and articles, theses, and books published in the literature. Document analysis was used as the data collection tool, and the data was organized and compared in the form of the opinions and problems of school administrators and teachers regarding the 4+4+4 education system. However, the research also revealed some concerns among school administrators and teachers regarding the 4+4+4 education system. Many respondents felt that they were not sufficiently informed about the system, and that it was implemented as a political decision rather than a wellplanned educational reform. They also expressed doubts about the benefits of reducing the age of compulsory education, and pointed out issues with inadequate physical infrastructure, particularly in terms of toilet facilities and staircases that were not suitable for younger students.In addition, some respondents were concerned that increasing the number of courses in middle schools could have a negative impact on student motivation, while the shortage of schools and classrooms made it difficult to implement the system effectively. Moreover, the elimination of the fifth grade in primary schools could lead to a surplus of teachers, creating problems with staffing and employment. Overall, while the 4+4+4 education system has its advantages, the concerns raised by school administrators and teachers indicate that there is still room for improvement and further research into the system's effectiveness. According to a research conducted among school administrators and teachers, the 4+4+4 education system has generally been positively received. The system is thought to have positive effects such as separating different age groups, increasing independent schools, improving vocational education, and making it easier for students and parents to choose schools. In addition, the opening of Imam Hatip secondary schools to provide reading opportunities for female students, early foreign language education, and the availability of elective courses in middle and high schools have also been considered positive.However, according to the data mentioned in the research, school administrators and teachers have thought that they were not adequately informed about the 4+4+4 education system. Additionally, some negative views have been expressed about the system such as it being a political decision, reducing the age of education not having positive results, toilets, bathrooms, and stairs not being suitable for 60-month-old students, increasing the number of courses in middle schools leading to a decrease in student motivation, not having enough schools and classrooms, inadequate physical infrastructure of schools, discipline problems increasing in schools due to the difficulty of repeating a grade, and many class teachers becoming surplus due to the closure of fifth grades in primary schools.